A argumentação em letras de músicas compostas e/ou cantadas pelo MST na perspectiva da teoria da polifonia e dos blocos semânticos - Slaviero, Angelice Melânia Barancelli (2008)
This work have the objective to expand the possibilities of application of the Arguments Theory in the language, especially the concepts of polyphony, proposed by Ducrot, and of semantic block, proposed by Marion Carel, producing a study that explain the meanings in the text created by argumentative threads, linked to the blocks her existing , with whom the speaker is identified. In view of this, the semantic blocks were determined repeatedly built in songs produced and / or sing by members of the MST, and the argumentative characteristics were drawn to the speaker responsible for the text listing text produced and / or sing and arguments repeated. It was found that the theory of Arguments in the language in the grounds of the Theory of Polyphony in Semantic Blocks, to show capacity to achieving the objectives. The analysis of songs enabled understand the argumentative senses, present in the texts, such as: fight, means triumph of power people to conquer the land, which is the place to produce the food; deal is to make produce the unproductive land; invade it a criminal act practiced by the Europeans, when reached in Latin America. The announcer, in letters from group A, is a self who is identified with the collective, while in group B, is a lonely that I have a lack of love, in an individual flight. These directions were evidenced in the threads of songs with no need to seek data or information in extra linguistics context. Thus, the ADL configures itself as a secure theoretical basis, able to give account of the understanding of the meanings set out in these texts for the analysis of language